Analisis Kadar Bioetanol Berbahan Baku Limbah Ampas Tebu (Saccharum officinarum) Campuran Kulit Jagung (Zea mays) pada Konteks Teknologi Ramah Lingkungan - Vazella Lavenia Lorenza; Rendy Wikrama Wardana; Ariefa Primair Yani; Purwanti Widhy Hastuti; M. Lutfi Firdaus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study purpose to see the levels of bioethanol produced by bagasse and corn husks with yeast, NPK and urea compositions. The method used in the study was an experiment with a predetermined ratio and fermentation time variables of 7, 14, and 21 days. Quantitative data were analyzed by calculating the average bioethanol levels and bioethanol volumes presented in table form. Meanwhile qualitative data were analyzed descriptively. The results showed that the highest bioethanol levels were in composition A (100% yeast) with a bioethanol content of 36,7% fermented for 21 days. The lowest bioethanol levels were in composition B (100% Urea) with a bioethanol content of 3,3% fermentation time of 7 days. The conclusion of this study shows that the volume of bioethanol has no effect on the levels of bioethanol produced, but this is not constant, because it can be influenced by other factors such as the duration of fermentation time, the materials used and the microbiological conditions during the fermentation process. Keywords: Sugarcane Bagasse, Bioethanol, Corn Husk, Environmentally Friendly Technology.